Current understanding of thermo(dys)regulation in severe burn injury and the pathophysiological influence of hypermetabolism, adrenergic stress and hypothalamic regulation: a systematic review - Mertin, Viktoria; Most, Patrick; Busch, Martin; Trojan, Stefan; Tapking, Christian; Haug, Valentin; Kneser, Ulrich; Hundeshagen, Gabriel (Burns & trauma, 2022)
In this systematic review, we summarize the aetiology as well as the current knowledge regarding thermo(dys)regulation and hypothermia after severe burn trauma and aim to present key concepts of pathophysiology and treatment options. Severe burn injuries with >20% total body surface area (TBSA) affected commonly leave the patient requiring several surgical procedures, prolonged hospital stays and cause substantial changes to body composition and metabolism in the acute and long-term phase. Particularly in severely burned patients, the loss of intact skin and the dysregulation of peripheral and central thermoregulatory processes may lead to substantial complications.A systematic and protocol-based search for suitable publications was conducted following the PRISMA guidelines. Articles were screened and included if deemed eligible. This encompasses animal-based in vivo studies as well as clinical studies examining the control-loops of thermoregulation and metabolic stability within burn patientsBoth experimental animal studies and clinical studies examining thermoregulation and metabolic functions within burn patients have produced a general understanding of core concepts which are, nonetheless, lacking in detail. We describe the wide range of pathophysiological alterations observed after severe burn trauma and highlight the association between thermoregulation and hypermetabolism as well as the interactions between nearly all organ systems. Lastly, the current clinical standards of mitigating the negative effects of thermodysregulation and hypothermia are summarized, as a comprehensive understanding and implementation of the key concepts is critical for patient survival and long-term well-being.The available in vivo animal models have provided many insights into the interwoven pathophysiology of severe burn injury, especially concerning thermoregulation. We offer an outlook on concepts of altered central thermoregulation from non-burn research as potential areas of future research interest and aim to provide an overview of the clinical implications of temperature management in burn patients.